Red onion (Allium ascalonicum L.) skin as an antibacterial on the growth of Staphylococcus aureus - Reza Anindita; Elva Dwi Pamungkas (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2023)
The main bacteria that cause infection in humans is Staphylococcus aureus. Efforts to prevent infectious diseases caused by bacteria can be made by using plant parts that have medicinal potential. One part of the plant that needs to be explored for its potential is the skin of shallot bulbs (Allium ascalonicum L.). This research aimed to determine the effect of red onion skin extract on the growth of 1. aureus bacteria. The research design is experimental. The samples in this study were 1 kg of red onion skin and a bacterial sub-culture of S. aureus ATCC: 25923. Extraction was carried out using the maceration method using 96% ethanol solvent and evaporated using a rotary evaporator and water bath. The antibacterial test was carried out by administering 30 µg chloramphenicol (positive control), sterile distilled water (negative control), and red onion skin extract with concentrations of 60%, 65%, 70%, and 75% with 3 repetitions. All treatments were given to S. aureus at 30 µL each using the Kirby-Baeur method. The research instrument was an observation sheet of the diameter of the inhibition zone. Data analysis used One-Way ANOVA. The results of this study show that ethanol extract of red onion skin with concentrations of 60%, 65%, 70%, and 75% was able to produce S. aureus inhibition zone diameters of 3.5 mm, 4 mm, 4.2 mm, and 4.3 mm. The results of the One-Way ANOVA test showed a significance value of 0.15 (sig>0.05), not proven to be able to significantly inhibit the growth of S. aureus. The conclusion shows that red onion skin extract as an antibacterial is not able to significantly inhibit the growth of S. aureus.